Early recognition of lung cancer by integrin targeted imaging in K‐ras mouse model. Issue 5 (14th January 2015) - Ermolayev, Vladimir; Mohajerani, Pouyan; Ale, Angelique; Sarantopoulos, Athanasios; Aichler, Michaela; Kayser, Gian; Walch, Axel; Ntziachristos, Vasilis
<x xml:space="preserve">Abstract</x> Non‐small cell lung cancer is characterized by slow progression and high heterogeneity of tumors. Integrins play an important role in lung cancer development and metastasis and were suggested as a tumor marker; however their role in anticancer therapy remains controversial. In this work, we demonstrate the potential of integrin‐targeted imaging to recognize early lesions in transgenic mouse model of lung cancer based on spontaneous introduction of mutated human gene bearing K‐ras mutation. We conducted ex vivo and fluorescence molecular tomography‐X‐ray computed tomography (FMT‐XCT) in vivo imaging and analysis for specific targeting of early lung lesions and tumors in rodent preclinical model for lung cancer. The lesions and tumors were characterized by histology, immunofluorescence and immunohistochemistry using a panel of cancer markers. Ex vivo, the integrin‐targeted fluorescent signal significantly differed between wild type lung tissue and K‐ras pulmonary lesions (PL) at all ages studied. The panel of immunofluorescence experiments demonstrated that PL, which only partially show cancer cell features were detected by αvβ3‐integrin targeted imaging. Human patient material analysis confirmed the specificity of target localization in different lung cancer types. Most importantly, small tumors in the lungs of 4‐week‐old animals could be noninvasively detected in vivo on the fluorescence channel of FMT‐XCT. Our findings demonstrated αvβ3‐integrin targeted fluorescent imaging to specifically detect premalignant pleural lesions in K‐ras mice. Integrin targeted imaging may find application areas in preclinical research and clinical practice, such as early lung cancer diagnostics, intraoperative assistance or therapy monitoring.